2011
DOI: 10.1159/000327969
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon-Performed Ultrasound as Preoperative Localization Study in Patients with Primary Hyperparathyroidism

Abstract: Background: Minimally invasive parathyroidectomy is the treatment of choice for single-gland primary hyperparathyroidism. However, the exact location of the abnormal gland has to be established. Sestamibi scintigraphy, computed tomography and ultrasound (US) are commonly used modalities. We describe our experience in a non-academic center with surgeon-performed US (S-US) of the neck as preoperative localization study in patients with primary hyperparathyroidism (PHPT). Methods: Patients with a biochemically pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…Other studies have found similar results including those by van Ginhoven et al. 12 with reported accuracy of 85%. Solorzano et al.…”
Section: Discussionsupporting
confidence: 81%
“…Other studies have found similar results including those by van Ginhoven et al. 12 with reported accuracy of 85%. Solorzano et al.…”
Section: Discussionsupporting
confidence: 81%
“…[6][7][8] Other studies focused on the advantage of clinic-based ultrasound in changing decisions about operative management of thyroid disease when compared to scans performed by a conventional ultrasound practitioner before the clinic visit. 9 Spurious lesions are frequent in head and neck ultrasound (Table III), commonly the result The process of palpation before the scan does not necessarily facilitate the ultrasound study.…”
Section: Discussionmentioning
confidence: 99%
“…The main drawback of US is related to its operator dependence resulting in highly variable localization. Some studies suggest improved sensitivity of parathyroid tumor localization with surgeon-performed US (rather than technician-or radiologist-performed US) (32,33). Other studies report improved sensitivity of parathyroid tumor localization when US was used in combination with sestamibi-SPECT (27).…”
Section: Preoperative Imagingmentioning
confidence: 99%